Greenhouse gas emission from construction stage of wooden buildings. (November 2014) - Takano, A.; Pittau, F.; Hafner, A.; Ott, S.; Hughes, M.; De Angelis, E.
<x content-type="archive" xml:space="preserve">Abstract</x> This study reports on a detailed investigation into the greenhouse gas emissions associated with the construction process of multistory wooden buildings relative to the other life cycle stages: the material production and operation stages. The results showed that the construction stage accounts for 20–30% of the initial embodied emissions and 6–10% of the total emission of the included life cycle stages. Especially the transport process of building components seems to have higher potential to mitigate the emissions than the actual construction work. In addition, the emissions from different construction systems were studied based on the reference buildings. Although definitive conclusion would be difficult to be drawn from this study alone due to the small sample size and the assumptions made, prefabrication work seems to be a more efficient construction method compared to on-site work for wooden buildings.